Communicative Functions of Umpasa in Toba Batak Traditional Ceremonies : Communicative Functions of Umpasa in Toba Batak Traditional Ceremonies - Daniel Binsah Lumban Gaol; Selviana Napitupulu; Bernieke Anggita Ristia Damanik (Journal of Applied Linguistics, 2026)
Umpasa is a fundamental oral tradition in Toba Batak culture, functioning as a medium for conveying blessings and spiritual messages. However, the functional shift between different ritual contexts, such as joyful weddings and solemn funerals, remains under-documented. This study aims to identify the types of communicative functions, determine their shifting dominance, and describe their linguistic realizations within Ulaon Unjuk and Ulaon Saur Matua. This research employs a qualitative descriptive method. The data consists of 20 selected umpasa utterances, analyzed using Roman Jakobson’s theory of communicative functions. The results reveal that only four of Jakobson’s six functions are present: poetic, conative, referential, and emotive. Phatic and metalingual functions are entirely absent, suggesting that umpasa is a fixed ritual text. Furthermore, function dominance is context-dependent. In Ulaon Unjuk, the poetic function is superior, as it prioritizes the aesthetic delivery of blessings and ancestral values through rhythmic metaphors. Conversely, in Ulaon Saur Matua, the conative function dominates, emphasizing the delivery of spiritual guidance, instructions, and social expectations for the bereaved family. These functions are realized through specific markers, such as nature-based metaphors and parallelism for the poetic function, and the optative particle "Sai" and address form "Hamu" for the conative function. In conclusion, umpasa serves as a sophisticated cultural vehicle that strategically adjusts its functional priority to reinforce cultural identity during major life transitions. Keywords : Communicative Functions; Pragmatics; Toba Batak Ethnics; Traditional Ceremonies; Umpasa